Educational Leadership in Remote Rural Settings: Identifying a Relevant Curriculum (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
This study explores educational leadership and curriculum relevance in DogadaKedar Rural Municipality, a remote area in Nepal. Through a two-day participatory workshop with head teachers and school management chairpersons, it examined local views on quality education and curriculum needs. Thematic analysis of discussions revealed key barriers: poverty, weak foundational learning, inadequate infrastructure, limited ICT use, teacher shortages, and student absenteeism due to economic pressures. Participants emphasized the need for vocational education, integration of local knowledge, and income-generating activities in schools to improve retention. A major research gap identified is the lack of bottom-up curriculum evaluation involving local stakeholders. The study critiques the dominance of centralized, policy-driven curricula that often overlook rural realities. It highlights the evolving role of educational leaders, who must adopt innovative, localized strategies in a competitive, neoliberal context. The study calls for greater municipal involvement in curriculum design and monitoring, promoting a more inclusive, accountable, and context-specific education system for rural Nepal.